The Interpretation Of Chinese Empress Dowager Cixi's Image In The Portraits Of American Artists - Margaryan, Ani (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
The Chinese themes in Early American art have long been obscured under the veil of Japonisme, Aesthetic movement, boundary-pushing modernism and more significantly because of the political circumstances - decline of China as an empire and complicated Chinese-American interconnections. One of the favoured theme of American academism at the period of the late 19th- early 20th centuries were genre scenes, street scenes, portrait d’intérieur1 , portraits, still life works related to China and Chinatowns. Nonetheless, the American press through the imagery created by illustrators and caricaturists was largely involved in interpretations of Western encounters with Chinese culture from the highlighted negative light, either being deeply affected by anti-Chinese flows or fuelling those xenophobic moods. Երկար ժամանակ չինական թեմաների արծարծումը վաղ ամերիկյան արվեստում «փակ» էր ճապոնականության, գեղագիտական շարժման, մոդեռնիզմի և, որ ավելի կարևոր է, քաղաքական հանգամանքների պատճառով. այն է` Չինաստանի՝ որպես կայսրության անկումը և չին-ամերիկյան բարդ հարաբերությունները: XIX դարի վերջին - XX դարասկզբի ամերիկյան ակադեմիզմի ամենասիրված թեմաներից էին Չինաստանի և Չինական թաղամասերի (Chinatown) հետ կապված ժանրային տեսարանները, փողոցային տեսարանները, դիմանկարները, նատյուրմորտները: Այնուամենայնիվ, ամերիկյան մամուլը նկարազարդողների և ծաղրանկարիչների ստեղծած պատկերների միջոցով մեծապես ներգրավված է եղել Չինաստանի և չինական մշակույթի պատկերն ընդգծված բացասական լույսի ներքո ներկայացնող մեկնաբանումների մեջ: Китайские темы в раннем американском искусстве долгое время были «закрыты» из-за Японизма, Эстетического движения, модернизма и, что наиболее важно, в силу политических обстоятельств упадка Китая как империи и сложных китайско-американских отношений. Одной из излюбленных тем американского академизма в конце XIX начале XX вв. были жанровые сцены, уличные сцены, портреты, натюрморты, связанные с Китаем и китайскими кварталами (Chinatown). Однако несмотря на это американская пресса посредством образов, созданных иллюстраторами и карикатуристами, была в значительной степени вовлечена в негативную интерпретацию образа Китая и китайской культуры. Следовательно, в этот период лишь немногие американские художники позитивно и сквозь призму восхищения изображали китайцев и китайскую среду.
Keywords: Արվեստագիտություն